Incidence and outcome of invasive candidiasis in intensive care units (ICUs) in Europe: results of the EUCANDICU project - Bassetti, Matteo; Giacobbe, Daniele R; Vena, Antonio; Trucchi, Cecilia; Ansaldi, Filippo; Antonelli, Massimo; Adamkova, Vaclava; Alicino, Cristiano; Almyroudi, Maria-Panagiota; Atchade, Enora; Azzini, Anna M; Carannante, Novella; et al. (Critical care (London, England), 2019)
BACKGROUND: The objective of this study was to assess the cumulative incidence of invasive candidiasis (IC) in intensive care units (ICUs) in Europe. METHODS: A multinational, multicenter, retrospective study was conducted in 23 ICUs in 9 European countries, representing the first phase of the candidemia/intra-abdominal candidiasis in European ICU project (EUCANDICU). RESULTS: During the study period, 570 episodes of ICU-acquired IC were observed, with a cumulative incidence of 7.07 episodes per 1000 ICU admissions, with important between-center variability. Separated, non-mutually exclusive cumulative incidences of candidemia and IAC were 5.52 and 1.84 episodes per 1000 ICU admissions, respectively. Crude 30-day mortality was 42%. Age (odds ratio [OR] 1.04 per year, 95% CI 1.02-1.06, p < 0.001), severe hepatic failure (OR 3.25, 95% 1.31-8.08, p 0.011), SOFA score at the onset of IC (OR 1.11 per point, 95% CI 1.04-1.17, p 0.001), and septic shock (OR 2.12, 95% CI 1.24-3.63, p 0.006) were associated with increased 30-day mortality in a secondary, exploratory analysis. CONCLUSIONS: The cumulative incidence of IC in 23 European ICUs was 7.07 episodes per 1000 ICU admissions. Future in-depth analyses will allow explaining part of the observed between-center variability, with the ultimate aim of helping to improve local infection control and antifungal stewardship projects and interventions.
Keywords: Candidemia; kandidóza invazivní; Humans; ICU; lidé středního věku; hodnocení výsledků zdravotní péče; Female; rizikové faktory; Aged; Abdominal candidiasis; senioři; lidé; Europe; infekce spojené se zdravotní péčí; ženské pohlaví; Male; jednotky intenzivní péče; Candidiasis, Invasive; Middle Aged; Retrospective Studies; Candidiasis; incidence; Incidence; retrospektivní studie; Intensive Care Units; mužské pohlaví; Outcome Assessment, Health Care; Evropa; Candida; Risk Factors; Cross Infection